2019
DOI: 10.1111/jgh.14667
|View full text |Cite
|
Sign up to set email alerts
|

Noneffectiveness of electroacupuncture for comorbid generalized anxiety disorder and irritable bowel syndrome

Abstract: Background and Aim Comorbid generalized anxiety disorder and irritable bowel syndrome are common and therapeutically challenging. We aimed to assess the effectiveness of electroacupuncture in relieving anxiety and bowel symptoms in Chinese adults with this form of comorbidity. Methods In a single‐blind randomized sham‐controlled trial, subjects with comorbid generalized anxiety disorder and irritable bowel syndrome were randomly assigned to receive 10 weekly sessions of electroacupuncture or sham electroacupun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…8 trials (16–18, 25–29) adopted sham acupuncture as the control group, among which the acupuncture total times ranged from 2 [25] to 28 [16], retention time ranged around 20–30 minutes per time, with a least acupuncture duration of 3 weeks [17, 26] and a most of 10 weeks [27]. The immediate efficacy (right at finishing treatments) of acupuncture treatments were recorded in 5 studies [16–18, 26, 28], 1 study examined acupuncture efficacy at 3 weeks post treatment [27], while 2 studies observed the efficacy at both the end of treatment and follow-up [25, 29].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…8 trials (16–18, 25–29) adopted sham acupuncture as the control group, among which the acupuncture total times ranged from 2 [25] to 28 [16], retention time ranged around 20–30 minutes per time, with a least acupuncture duration of 3 weeks [17, 26] and a most of 10 weeks [27]. The immediate efficacy (right at finishing treatments) of acupuncture treatments were recorded in 5 studies [16–18, 26, 28], 1 study examined acupuncture efficacy at 3 weeks post treatment [27], while 2 studies observed the efficacy at both the end of treatment and follow-up [25, 29].…”
Section: Resultsmentioning
confidence: 99%
“…Coming to the Chinese research [16], a fixed formula using acupuncture of daily 30 minutes' retention over 4 weeks equaling 28 sessions was compared with sham control, nonacupoints, 2 cm bilateral, perpendicular needling with no manipulation for the same course. Otherwise, the acupuncture parameters in the 5 RCTs [2529] with negative results about the biological effects of acupuncture were not adequate in formula design. 3 studies [25, 27, 29] punctured for once a week or even once biweekly, totaling for 10 sessions or 2 times in total.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations